Strategi Digitalisasi sebagai Solusi Pemasaran UMKM : Studi pada Warung Sarapan Tiga Dara di Medan Area - Siti Khairani; Istiaza Azra; Zainarti Zainarti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research discusses the strategic role of MSMEs in the Indonesian economy and explores digitalization as a marketing solution to overcome challenges such as less strategic location and low digital literacy. The aim is to investigate the impact of digitalization on MSME marketing strategies, particularly in improving operational efficiency and market reach. The method used is qualitative with a literature review from credible sources such as books and scientific journals. The results show that digitalization significantly improves the marketing effectiveness of MSMEs, as in the case study of Warung Sarapan Tiga Dara which is able to overcome location limitations by utilizing social media and digital tools to reach a wider audience. In conclusion, the implementation of digital marketing strategies is essential for MSMEs to thrive in a competitive environment by improving operational efficiency, customer engagement, and business sustainability despite location constraints.